Testing of Acoustic Sensor of Powerful Nanosecond Pulses - Vdovin V. A.; Andreev V. G.; Afanasev K. V.; El'chaninov A. A. Anton Aleksandrovich; Klimov A. I. Aleksey Ivanovich (Oral Session, 2010)
Title screen